Prove that:

Is this correct?

L.H.S

= n.B(m, n -1) , where B(x, y) is Beta function

= n. m!(n-1)!/((m + n - 1 + 1)!)

= n(n-1)!m!/((m+n)!)

= R.H.S

Printable View

- Feb 10th 2009, 01:55 PMfardeen_genBeta function?
Prove that:

Is this correct?

L.H.S

= n.B(m, n -1) , where B(x, y) is Beta function

= n. m!(n-1)!/((m + n - 1 + 1)!)

= n(n-1)!m!/((m+n)!)

= R.H.S - Feb 10th 2009, 04:22 PMNonCommAlg
that's not a proof! you're using what you're supposed to prove! do it by induction: fix an and do the induction over nothing to prove for n = 1. so suppose the claim is true for

let since we have:

on the other hand by integration by parts: which with (1) gives us: